Broadband GaN HEMT distributed power amplifier design with phase adjustment. Issue 1 (1st December 2017) - Yan, Huan Hui; Kumar, Narendra; Latef, Tarik Abdul; Yarman, Binboga Siddik; Grebennikov, Andrei
Abstract: This letters presents a new wideband power amplifier approach to achieve high performance of wideband frequency operation from low frequency such as 80–2100 MHz for two‐way radio applications. The approach is referring to distributed power amplifier with phase adjustment of the gate line network to balance with drain line network (specifically with drain line tapering). Experimental of the prototype level with gallium nitride high‐electron‐mobility‐transistor demonstrated output power of 41 dBm, flat gain at 12 dB, and bandwidth covering 80 MHz to 2.1 GHz with power added efficiency of 45% under 28 V drain bias. According to the author's knowledge, this work has illustrated a significant enhancement in efficiency over the conventional topology, low cost implementation, and offers wideband operation for public safety applications.